2007
DOI: 10.1086/519965
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Colony Social Organization in Fire Ants: An Integrative Overview

Abstract: Expression of colony social organization in fire ants appears to be under the control of a single Mendelian factor of large effect. Variation in colony queen number in Solenopsis invicta and its relatives is associated with allelic variation at the gene Gp-9, but not with variation at other unlinked genes; workers regulate queen identity and number on the basis of Gp-9 genotypic compatibility. Nongenetic factors, such as prior social experience, queen reproductive status, and local environment, have negligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
132
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(135 citation statements)
references
References 129 publications
(216 reference statements)
3
132
0
Order By: Relevance
“…Genetically determined ARTs that could represent ESS occur in several species of fish [28], lizards [27], in ruffs (Philomachus pugnax) [29] and in the isopod Paracerceis sculpta [30]. In fire ants (Solenopsis invicta), the number of breeding queens per colony is determined by the single gene Gp-9, with one queen (monogynous social organization) when only the B-allele is present, but multiple queens ( polygynous social organization) when the b-allele is present as well [31]. The existence of male ARTs alone might not change the social organization unless females also show ARTs [15], but only in a few species do both sexes show ARTs.…”
Section: Genetic Variationmentioning
confidence: 99%
“…Genetically determined ARTs that could represent ESS occur in several species of fish [28], lizards [27], in ruffs (Philomachus pugnax) [29] and in the isopod Paracerceis sculpta [30]. In fire ants (Solenopsis invicta), the number of breeding queens per colony is determined by the single gene Gp-9, with one queen (monogynous social organization) when only the B-allele is present, but multiple queens ( polygynous social organization) when the b-allele is present as well [31]. The existence of male ARTs alone might not change the social organization unless females also show ARTs [15], but only in a few species do both sexes show ARTs.…”
Section: Genetic Variationmentioning
confidence: 99%
“…In addition, recognition of phenotypic cues by allele matching (recognition-allele mechanism), may also occur (Keller and Ross, 1998). For example, in fire ants, Gp-9 genotypic compatibility seems to regulate queen identity and number via production of a distinct chemical label and formation of a specific exclusionary template based on the allelic variant possessed by workers and queens (Gotzek and Ross, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that Gp-9 codes for an odorant-binding protein (OBP), coupled with evidence that selection acted to drive the molecular divergence of Gp-9b alleles from the ancestral Gp-9B allele, has led to the suggestion that this gene may have a direct role in regulating social organization by means of chemical communication 7,13 . However, because it is unlikely that an OBP also affects traits as diverse as female size, female fecundity and male spermatogenesis, it has been suggested that Gp-9 might be part of a supergene comprising many genes in tight linkage 10,12,14 . The existence of such clusters of loci facilitating the co-segregation of adaptive variation has been demonstrated in some classical cases of floral types (for example, ref.…”
mentioning
confidence: 99%
“…However, because it is unlikely that an OBP also affects traits as diverse as female size, female fecundity and male spermatogenesis, it has been suggested that Gp-9 might be part of a supergene comprising many genes in tight linkage 10,12,14 . The existence of such clusters of loci facilitating the co-segregation of adaptive variation has been demonstrated in some classical cases of floral types (for example, ref.…”
mentioning
confidence: 99%